Antimicrobial potential of seaweed epiphytic bacteria against nosocomial pathogens (International Journal of Food and Nutritional Sciences, 2022)
Seaweed Epiphytic microorganisms have transformed into a critical goal for the biotechnology business because of the tremendous number of bioactive blends actually found from them. In this current review, the antimicrobial strains were isolated from Seaweed gathered from Bay of Mannar, South east shore of India. Totally 101 organisms were isolated from five particular Seaweed. Ethyl acidic corrosive